Optical switching - Papadimitriou, G. I. (Wiley-Interscience, 2007)
While much has been published on the subject in individual articles, this text is the first to cohesively present optical switching in a single book. The three authors examine and discuss all the challenges involved in the commercialization of optical switching. Readers are brought up to date with the latest advances in research as well as the technological hurdles that researchers.